Translation and Psychometric Evaluation of Clinical Performance Assessment Scale among Nursing Students - Maryam Esmaeili; Sina Valiee; Sina Valiee; Zohreh Parsa-yekta; Abbas Ebadi (Kerman University of Medical Sciences, 2013)
Background & Objective: Effective bedside care is the main objective of nursing education Correct clinical evaluation of students has been one of the toughest tasks for clinical nursing lecturers The objective of this study was the translation and psychometric evaluation of the clinical performance assessment scale among nursing students in Iran Methods: This crosssectional study was conducted with the objective of validating the Iranian version of the nursing students performance scale within the clinical setting The scale was translated from English into Persian by the backward and forward method Its face and content validities were determined 2 items was added in the content and face validity process In order to determine the construct validity exploratory factor analysis by convenience sampling method was carried out on 275 senior nursing students within clinical educational settings for 5 months Evaluation was conducted according to this scale Cronbachs alpha coefficient was used to measure internal consistency Results: The mean and standard deviation of students scores was 6398 ± 1335 Factor analysis indicated the extraction of three factors: the nursing process (10 items eigenvalue 899) professional behaviors (16 items eigenvalue 797) and technical skills (2 items eigenvalue 203) The reliability of the scale obtained by Cronbachs alpha coefficient was 092 Conclusion: The results of psychometric evaluation of the clinical performance assessment scale vindicated the reliability and validity of this scale and the potential for using this instrument in the nursing education field in Iran However the inclusion of the technical skills factor would need further balancing and expansion